MENANAMKAN SEMANGAT BELA NEGARA MELALUI PROGRAM “PAHLAWANKU, PAHLAWANMU” PADA ANAK PANTI ASUHAN - Nayla Trihapsari; Berta Marcelina; Cut Huriyya 'Aqila Zichra; Nandita Afra Renata; Sri Rahma Aulia; Nabil Arij Fannan; Yohanes Christiano MT; Rafinda Rahmat; Febiyola Bungas Permata; Andiny Putri Vanosha; Ripi Hamdani (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The spirit of national defense needs to be instilled from an early age to shape the character of the younger generation who have a sense of love for the homeland, nationalism, and responsibility as citizens. Children in orphanages are one group that requires strengthening national values ​​through activities that are appropriate to their characteristics. This study aims to describe the implementation of the "My Hero, Your Hero" program and its role in instilling the spirit of national defense in orphanage children. The study used a qualitative approach with a descriptive type. The study was conducted at the Al Muzakki Orphanage involving 10 children as research subjects. Data were collected through observation, interviews, and documentation, then analyzed descriptively. The results of the study indicate that the "My Hero, Your Hero" program can be implemented well through the delivery of materials, inspirational stories, discussions, questions and answers, and educational games. Participants showed high enthusiasm during the activity and were able to understand the meaning of national defense and its application in everyday life. This program plays a role in increasing participants' understanding of the values ​​of heroism, nationalism, discipline, responsibility, and social care. The "My Hero, Your Hero" program can be an alternative educational activity to support the instillation of the spirit of national defense and the formation of children's character in the orphanage environment.